Demons, Saviours, and Narrativity in a Vernacular Literature - Villarea, University of the Philippines, Diliman, Corazon D. (Asiatic: IIUM Journal of English Language and Literature, 2010)
Narratives from and on Panay and Negros in the Western Visayas region of the Philippines are generally called the sugilanon. Its origins are usually traced to the Visayan epics; the sugilanon receded in the background with the dominance of religio-colonial literature in the Spanish period (1660's-1898) but re-emerged as didactic narratives with the publication of popular magazines in Visayan in the 1930's. Tracking its development could be a way of writing a literary history of the region. Â  Â  The last 25 years has been a particularly exciting time in its development. Young, schooled writers are now writing with the â€œinstinctualâ€ writers, in a variety of languages, Hiligaynon, Kiniray-a, Filipino and even English and experiments in craft are evident. The study focuses on sugilanon in this period, in particular the sub-genre utilising spiritlore as part of its imaginative repertoire. It explores the creative transformations of spirit-lore both in theme and narrative method in the sugilanon. Moreover, it seeks to explain the persistence of demons, dungans and other spirits even among writers with supposedly post-modern sensibilities. This may be attributed to residuality or to metaphorical ways of seeing. But the paper argues that spirit-lore is very much tied up with notions of social agency and historical continuity. Such questions could illuminate some aspects of narrativity in the vernacular.